Network Pharmacology Reveals Polyphyllin II as One Hit of Nano Chinese Medicine Monomers against Nasopharyngeal Carcinoma - Meng-Zhe Yang; Bei-Bei Zhang; Jian-Chun Huang; Xian-Yu Bai; Zhen-Qiang Liang; Xiang Yi; Ning Xu; Yuan-Jiao Huang; Ai-Jun Jiao (Bioinorganic Chemistry and Applications)
Nasopharyngeal carcinoma (NPC) is a malignant tumor in southern China, and nano Traditional Chinese Medicine (TCM) represents great potential to cancer therapy. To predict the potential targets and mechanism of polyphyllin II against NPC and explore its possibility for the future nano-pharmaceutics of Chinese medicine monomers, network pharmacology was included in the present study. Totally, ninety-four common potential targets for NPC and polyphyllin II were discovered. Gene Ontology (GO) function enrichment analysis showed that biological processes and functions mainly concentrated on apoptotic process, protein phosphorylation, cytosol, protein binding, and ATP binding. In addition, the anti-NPC effects of polyphyllin II mainly involved in the pathways related to cancer, especially in the PI3K-Akt signaling indicated by the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. The “drug-target-disease” network diagram indicated that the key genes were SRC, MAPK1, MAPK14, and AKT1. Taken together, this study revealed the potential drug targets and underlying mechanisms of polyphyllin II against NPC through modern network pharmacology, which provided a certain theoretical basis for the future nano TCM research.